EFEKTIVITAS EDUKASI PERSONAL HYGIENE TERHADAP PENINGKATAN PENGETAHUAN SANTRI DI MTSS AL-FALAH KOTA PADANG - Wira Iqbal; Aria Gusti; Frima Elda; Fadilla Azmi (MINDA BAHARU, 2026)
Abstract. Personal hygiene is an important aspect in preventing infectious diseases, particularly in Islamic boarding schools where students live in a communal environment with a high risk of environmentally based disease transmission. This community service activity aimed to analyze the effect of personal hygiene education on the knowledge level of seventh-grade students at Al-Falah Islamic Boarding School in Padang City. A pre-experimental method with a one-group pre-test and post-test design was applied. The sample consisted of 53 seventh-grade students selected using purposive sampling. Data were collected using a validated personal hygiene knowledge questionnaire. Data analysis was conducted descriptively and inferentially using a paired t-test. The results showed that the average pre-test score was 89.43, while the average post-test score increased to 90.19, with a mean difference of 0.75 points. Statistical analysis indicated a significant difference between pre-test and post-test scores (p < 0.05). Although the increase in knowledge was relatively small, personal hygiene education was proven to have a significant effect on improving students’ knowledge. These findings highlight the importance of implementing continuous and innovative health education programs to promote clean and healthy living behaviors in Islamic boarding school settings.